Severe digital ischemia as an unrecognized manifestation in patients with antisynthetase autoantibodies: Case series and systematic literature review. Issue 3 (October 2022) - Yoshida, Akira; Gono, Takahisa; Okazaki, Yuka; Shirai, Yuichiro; Takeno, Mitsuhiro; Kuwana, Masataka
Objective: Severe digital ischemia, including digital ulcers and gangrene, is considered rare in patients with antisynthetase antibodies. This study aimed to elucidate the clinical features of antisynthetase-positive patients complicated with digital ulcers and/or gangrene using a systematic literature review and case series in a single-center cohort. Methods: A systematic literature review was conducted to identify reports describing antisynthetase-positive cases with digital ulcers and/or gangrene. Our cohort of consecutive patients with antisynthetase antibodies was stratified by the history of severe digital ischemia. Demographic and clinical features and outcomes in patients with severe digital ischemia identified in the systematic literature review and our cohort were compared with those in patients without severe digital ischemia in our cohort. Results: The systematic literature review revealed 12 antisynthetase-positive patients with severe digital ischemia from one case series and eight case reports. Seven (7%) of 100 patients with antisynthetase antibodies in our cohort had a record of severe digital ischemia. Severe digital ischemia was often found at presentation and was associated with the classification of systemic sclerosis with or without myositis overlap. Clinical features associated with severe digital ischemia in antisynthetase-positive patients included Raynaud's phenomenon ( p < 0.001), digital pitting scars ( p = 0.001), and nailfold capillary abnormality ( p = 0.02). Outcomes of severe digital ischemia were generally favorable with vasodilators. Conclusion: Severe digital ischemia is an overlooked complication in antisynthetase-positive patients. Antisynthetase antibodies should be measured in patients presenting with digital ulcers or gangrene, especially in those with systemic sclerosis phenotype and features associated with antisynthetase antibodies in the absence of systemic sclerosis-specific autoantibodies.